Lactate to albumin ratio has limited prognostic value for complications in children under five with burn injuries - Cadarso-Saez, Vania (2025)
Evaluate the prognostic performance of the lactate-to-albumin ratio (LAR) for complications in children 5 years of age or younger with second and/or third degree burn injuries during hospitalization in the intensive care unit of a hospital in Lima, Peru. In this retrospective cohort study, we conducted prognostic tests by analyzing the medical records of children aged ≤ 5 years who suffered second- and/or third-degree burn injuries and were subsequently admitted to the ICU of a Lima-based hospital between 2017 and 2022. The LAR was calculated using lactate and albumin values measured within the first 48 h post-burn. The area under the curve (AUC) was utilized to evaluate the prognostic performance of the LAR in predicting complications. A cohort of 258 patients aged ≤ 5 years with second- and/or third-degree burn injuries was examined. Among them, 63 patients experienced complications (24.4%). The estimated AUC ROC for the LAR was 0.63 (95% confidence interval [CI]: 0.54–0.71). After adjusting for confounders, values of LAR above the threshold were found to be associated with a significantly increased risk of complications (adjusted relative risk: 2.23; 95% CI 1.51–3.29; p < 0.001). The LAR exhibited limited prognostic capability for complications in pediatric burn patients. Nevertheless, a significant association was observed between values of LAR above the threshold and increased risk of complications.